Standardization And Phytochemical Testing Of Purple Leaf Simplicia (Graptophyllum Pictum) - Farah Aulia Azzahra; Heldi Candra (Bajang Institute, 2026)
Background: Purple leaf (Graptophyllum pictum) is a medicinal plant widely used in traditional medicine due to its bioactive compounds, including flavonoids, alkaloids, and steroids. To ensure its safety, quality, and efficacy as a herbal raw material, standardization and phytochemical evaluation are essential. Objective: This study aimed to determine the standardization parameters and phytochemical characteristics of purple leaf simplicia. Methods: The study employed qualitative and quantitative approaches. Purple leaves were cultivated, harvested, processed into simplicia powder, and extracted using the maceration and Soxhlet methods with 96% ethanol. Standardization included moisture content, drying loss, total ash, water-soluble extractive value, ethanol-soluble extractive value, and thin-layer chromatography (TLC) analysis. Data were analyzed descriptively. Results: The cultivation process produced 9 g of simplicia powder. The moisture content, drying loss, total ash, water-soluble extractive value, and ethanol-soluble extractive value were 47.3%, 27.6%, 21.7%, 0.227 g, and 10 g, respectively. Soxhlet extraction yielded 20 mL of concentrated extract. Thin-layer chromatography analysis under UV 254 nm produced Rf values of 0.625, 0.750, and 0.8125, indicating the presence of phytochemical constituents in the extract. Conclusion: Purple leaf simplicia can be successfully standardized using physicochemical parameters and TLC analysis. The findings provide baseline information for quality control and support the utilization of Graptophyllum pictum as a potential raw material for herbal medicine development